Pengaruh Kecerdasan Interpersonal Kepala Sekolah Terhadap Produktivitas Sekolah Dasar - Syafrudin; Sudadio; Sholeh Hidayat (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
This study aims to analyze and describe the influence of interpersonal intelligence leadership competence of school principals on the productivity of elementary schools in Serang City. This research was conducted in Elementary Schools, Serang City, Banten Province which are spread over six sub-districts, namely Cipocok Jaya, Curug, Kasemen, Taktakan, Walantaka, and Serang. This research is a research with a quantitative approach using ex post facto survey research methods. This research method was chosen by considering the problems and the purpose of this study, namely to analyze the effect of the managerial competence of school principals on the productivity of elementary schools in Serang City. In addition, this research data was collected not necessarily through treatment that was deliberately carried out by researchers but the data collected was already available in the field and owned by the respondents so that only required instruments in the form of a questionnaire to collect these data. After conducting research, it was found that there was no positive direct effect of interpersonal intelligence on school productivity in the scope of Elementary Schools in Serang City, Banten Province. This explains that increasingly adequate interpersonal intelligence has not been able to have a positive impact on increasing school productivity in the scope of Elementary Schools in Serang City, Banten Province